Painless solitary mastoid osteoma: a rare presentation - Prajapati, Manish A.; Joshi, Anagha A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
The benign tumors of the temporal bone, such as osteomas, are rare. Osteomas are typically slow-growing benign tumors composed of mature bone tissue. They occasionally occur in the external auditory canal; however, they are reported to be even rarer in the mastoid bone. A 30-year-old female presented to our department in a tertiary care hospital with a hard swelling behind the left ear, diagnosed as osteoma on HRCT temporal bone scan. A complete excision was done using a postauricular approach. Histopathology confirmed the diagnosis of osteoma. Osteomas, although rare, should be considered when dealing with any hard mastoid swelling. Drilling can ensure complete removal until the normal cortical bone is reached to avoid recurrence. A cortical mastoidectomy should be done if the mastoid air cell system is involved.